Ottomans, Safavids, and Mughals: From the Peak of Glory to the Political Fragmentation of the 18th Century - Jabal Rahmah; Basri Basri; Yusri Handayani; Ana Dhiqfaini Sultan; Rahmawati Rahmawati (Lembaga Yasin AlSys, 2025)
This study investigates the decline of three major Islamic empires in the 18th century—the Ottoman Sultanate, the Safavid Dynasty, and the Mughal Dynasty—which had previously attained prominence in political, military, and cultural spheres. The research aims to analyze the internal and external factors that led to the political fragmentation of these empires. Adopting a qualitative approach with a historical-comparative method, the study relies on literature-based data, which were analyzed through five stages: heuristics, verification, interpretation, comparison, and historiography. The findings indicate that the decline of these empires resulted from an interplay between internal weaknesses, including leadership crises, succession conflicts, and the decentralization of power, and external pressures stemming from European colonial expansion and transformations in the global economic system. The study concludes that, despite political fragmentation, the cultural and religious legacies of these empires continue to shape the development of the Islamic world in contemporary contexts. The research contributes to a deeper understanding of the transition from cohesive imperial power to fragmented political entities and elucidates broader changes in global dynamics during this period.